The Impact of Green Taxes on Regional Tax Revenue and Environmental Sustainability: Evidence from Makassar City - Marlinah, Andi; Rachma, Nur (LifeSciFi, 2025)
The global environmental crisis demands innovative solutions that integrate economic and ecological objectives. Green tax has emerged as a strategic fiscal policy instrument that not only aims to correct negative externalities but also has the potential to increase regional revenue. This study aims to examine the effect of implementing a green tax on regional tax revenue and environmental sustainability, focusing on the non-cyclical consumer sector. The research method used was a quantitative approach with stratified random sampling of 50 respondents (tax officials, business actors, and the public). Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the green tax has a positive and significant effect on both dependent variables. Specifically, the green tax has a strong effect on environmental sustainability (path coefficient = 0.645; p-value = 0.000) and a significant effect on regional tax revenue (path coefficient = 0.532; p-value = 0.000). These findings confirm that green taxes can be a dual solution: a source of fiscal revenue and a tool to encourage the transition to sustainable development.